Unambiguous observation of shape effects on cellular fate of nanoparticles - Chu, Zhiqin; Zhang, Silu; Zhang, Bokai; Zhang, Chunyuan; Fang, Chia-Yi; Rehor, Ivan; Cigler, Petr; Chang, Huan-Cheng; Lin, Ge; Liu, Renbao; Li, Quan (Scientific reports, 2014)
Cellular fate of nanoparticles is vital to application of nanoparticles to cell imaging, bio-sensing, drug delivery, suppression of drug resistance, gene delivery, and cytotoxicity analysis. However, the current studies on cellular fate of nanoparticles have been controversial due to complications of interplay between many possible factors. By well-controlled experiments, we demonstrated unambiguously that the morphology of nanoparticles independently determined their cellular fate. We found that nanoparticles with sharp shapes, regardless of their surface chemistry, size, or composition, could pierce the membranes of endosomes that carried them into the cells and escape to the cytoplasm, which in turn significantly reduced the cellular excretion rate of the nanoparticles. Such features of sharp-shaped nanoparticles are essential for drug delivery, gene delivery, subcellular targeting, and long-term tracking. This work opens up a controllable, purely geometrical and hence safe, degree of freedom for manipulating nanoparticle-cell interaction, with numerous applications in medicine, bio-imaging, and bio-sensing.
Keywords: Nanoparticles; buněčné linie; povrchové vlastnosti; nanočástice; Intracellular Space; Cell Line; biologický transport; lidé; Humans; intracelulární prostor; Biological Transport; Surface Properties